(untitled) (Práxis Educativa, 2019)
O objetivo principal deste artigo é apresentar o espaço da pesquisa em Educação Física (EF) no contexto escolar e da Formação de Professores (FP), em 25 anos do Programa de Pós-Graduação em Educação (Mestrado/Doutorado) da Universidade Estadual de Ponta Grossa (PPGE/UEPG). A partir de uma abordagem quanti-qualitativa, de um estudo de caso, descritivo, são explicitados os principais aspectos da produção acadêmica no âmbito da EF no contexto escolar e da FP no PPGE/UEPG. O estudo circunscreve-se aos anos de implantação do Mestrado (1994) e do Doutorado (2010), considerando-se a produção acadêmica de 1996 a 2018. Destacam-se os fatos que contribuíram para fomentar a produção acadêmica no âmbito da EF no contexto escolar e da FP no PPGE/UEPG. Verifica-se que o espaço dos saberes e dos conhecimentos da EF e da FP foi ampliado significativamente em 25 anos do PPGE/UEPG. Palavras-chave: Educação Física. Formação de professores. Pós-Graduação em Educação. Abstract Research on Physical Education in the school context and of teacher education in the Graduate Program in Education at the State University of Ponta Grossa (1994-2010) The main purpose of this article is to present the research space in Physical Education in the school context and of teacher training in 25 years of the Graduate Program in Education (Master’s/Doctorate) of the State University of Ponta Grossa (Universidade Estadual de Ponta Grossa - UEPG). From a quantitative and qualitative approach, of a descriptive case study, the main aspects of the academic production within the Physical Education in the school context and of teacher training in Master’s/Doctorate of the UEPG are set out. The study is limited to the years of implementation of the Master’s (1994) and Doctorate (2010), considering the academic production from 1996 to 2018. The facts that contributed to foster the academic production within the Physical Education in the school context and training of the Physical Education Teacher of the Master’s/Doctorate are highlighted. It turns out that the space of expertise and knowledge of Physical Education and training of the Physical Education Teacher was expanded significantly in the 25 years of the UEPG Graduate Program in Education. Keywords: Physical Education. Teacher training. Graduate Program in Education. Resumen La investigación en Educación Física en el contexto escolar y de la formación de profesores en el Postgrado en Educación en la Universidad Estatal de Ponta Grossa (1994-2010) El objetivo principal de este artículo es presentar el espacio de investigación en Educación Física (EF) en el contexto escolar y de Formación de profesores (FP) en 25 años del Programa de Formación de Postgrado (Maestría/Doctorado) en la Universidad Estatal de Ponta Grossa (Universidade Estadual de Ponta Grossa - UEPG). A partir de un enfoque cuantitativo y cualitativo, un estudio de caso descriptivo, son explicados los principales aspectos de la producción académica en el ámbito de la EF en el contexto escolar y FP en PPGE/UEPG. El estudio se limita a los años de implementación de la Maestría (1994) y Doctorado (2010), considerando la producción académica de 1996 a 2018. Se destacan los hechos que contribuyeron a fomentar la producción académica en el ámbito de la EF en el contexto escolar y FP en PPGE/UEPG. Se verifica que el espacio de los saberes y de los conocimientos de la EF y del FP se amplió considerablemente en 25 años de PPGE/UEPG. Palabras-clave: Educación Física. Formación de los docentes. Certificado de Postgrado en Educación.